The Reformation and Its Implication for Today’s Church - Chongloi, Kamminlun (LPPM IAKN Tarutung, 2022)
The Roman Church in the 13th- 15th century suffered a severe deviation from the truth in both the ecclesiastical life and in the dogma. Corruption crept into the Church and the clergy forgot their pastoral responsibilities. Instead, they looked after their own personal pleasures. The leadership and the church administration was not in the way it should be. People during the Middle Ages in Europe had a very real dread of the period of punishment in purgatory and hell, which were graphically portrayed in the ChurchThis research materials is taken from the textbooks, journals and other written materials. The issues which were dealt with by the reformer are still very much prevalent; today in the church, universally and locally. Likewise, the present churches today as a whole is plagued with internal issues such as corruption, fight for leadership, interest for own benefits by the leaders, moral degradation of the members as was cited in the research paper.